Evaluation of the Possibility for Non-oral Enteral Feeding in Acute Pancreatitis Patients by Using PASS (Pancreatitis Activity Scoring System) - Kim, Song-Hwan; Jong, Nam-Hun; Kim, Hye-Song; Yu, Nam; Choe, Jong-Hwa; Ri, Un-Hui; Jong, Sin-Hyok; Ri, Song-Ung; Ri, Chol-Su (Medical Science Journal for Advance Research, 2026)
Purpose: Our purpose is to set up the new criteria for initiating NOEF(non-oral enteral feeding) safely in acute pancreatitis patients by analyzing several univariate indices and multivariate clinical scoring systems measured in the early days of NOEF. Methods: We involved moderately severe and severe acute pancreatitis patients who received NOEF treatment. We made a univariate and multivariate analysis of all the demographical, clinical, laboratory, radiological indices and clinical scores before NOEF, to find out the independent evaluation factors of paralytic ileus during NOEF. By analyzing ROC(receiver operating characteristics) curve, optimal cut-off points of selected independent risk factors were defined. We determined the ranges below the cut-off points as the safe ranges out of paralytic ileus during NOEF. Results: A total of 136 patients was involved in our study. By the univariate analysis, abdominal pain, respiratory rate, body temperature, rebound tender on physical examination, band neutrophil count, SIRS(systemic inflammatory response syndrome) score, PASS(pancreatitis activity scoring system), BISAP(bedside index of severity in acute pancreatitis), Balthazar score were associated with occurrence of paralytic ileus during NOEF(P<0.05). By the multivariate analysis, respiratory rate and PASS were selected as the independent risk factors of paralytic ileus during NOEF(P<0.05). Areas under ROC curves(AUROCs) of respiratory rate and PASS in predicting paralytic ileus were 0.873(0.777-0.970), 0.897(0.795-0.999), respectively. The optimal cut-off points of highest odds ratios(OR) and negative predictive values(NPV) in predicting paralytic ileus after NOEF were respiratory rate≧25bpm and PASS≧120, respectively. Conclusion: Safe range for NOEF during acute pancreatitis treatment is PASS<120 or respiratory rate<25bpm.